A second gene, VpreB in the lambda 5 locus of the mouse, which appears to be selectively expressed in pre-B lymphocytes. - Kudo, A (1987)
The murine gene lambda 5 is selectively expressed in pre-B lymphocytes. Of the three exons encoding lambda 5, exons II and III show strong homologies to immunoglobulin lambda light (L) chain gene segments, i.e. to J lambda intron and exon, and C lambda exon sequences respectively. We have now found, 4.6 kb upstream of lambda 5, another gene composed of two exons which is selectively expressed in pre-B cell lines as a 0.85 kb mRNA potentially coding for a protein of 142 amino acids including a 19 amino acid-long signal peptide. The 5' sequences of this gene show homologies to sequences encoding the variable regions of kappa and lambda L chains and of heavy (H) chains. The deduced amino acid sequence contains the consensus cysteine residues as well as other consensus amino acids at positions which characterize immunoglobulin (Ig) domains. We call the second gene VpreB. The 3' end of VpreB encoding the 26 carboxyl terminal amino acids shows no homology to any known nucleotide sequence. The putative protein encoded by VpreB is a potential candidate for association with the putative protein encoded by lambda 5, and thereby a candidate for association with H chains in pre-B cells. Southern blot analysis of DNA from liver (germ line) and 70Z/3 pre-B cell lines reveals two genes which hybridize to the VpreB gene. We call VpreB1 the gene which is found 5' of lambda 5. The other gene, called VpreB2, which has not yet been located within the genome, shows 97% nucleotide sequence homology to VpreB1 in an area of 1 kb which covers the coding region of the gene.(ABSTRACT TRUNCATED AT 250 WORDS)